2016
DOI: 10.3897/zookeys.605.7136
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships within the Phyllidiidae (Opisthobranchia, Nudibranchia)

Abstract: The Phyllidiidae (Gastropoda, Heterobranchia, Nudibranchia) is a family of colourful nudibranchs found on Indo-Pacific coral reefs. Despite the abundant and widespread occurrence of many species, their phylogenetic relationships are not well known. The present study is the first contribution to fill the gap in our knowledge on their phylogeny by combining morphological and molecular data. For that purpose 99 specimens belonging to 16 species were collected at two localities in Indonesia. They were photographed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Distribution of specific taxa is highly variable when comparing the different localities in BA (Table 2), with Chromodoris annae (46 individuals) and Phyllidiella pustulosa (39 individuals) dominating the overall collection and being encountered in almost all sites. Unpublished results confirm earlier results from Stoffel et al [25] and clearly show cryptic speciation in Phyllidiella pustulosa, with sympatric occurrences of the various clades in Bangka Archipelago, BNP, and the island of Sangihe. If these clades are considered separate species, the diversity would increase by five to seven species and thus render P. pustulosa a much less common species.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Distribution of specific taxa is highly variable when comparing the different localities in BA (Table 2), with Chromodoris annae (46 individuals) and Phyllidiella pustulosa (39 individuals) dominating the overall collection and being encountered in almost all sites. Unpublished results confirm earlier results from Stoffel et al [25] and clearly show cryptic speciation in Phyllidiella pustulosa, with sympatric occurrences of the various clades in Bangka Archipelago, BNP, and the island of Sangihe. If these clades are considered separate species, the diversity would increase by five to seven species and thus render P. pustulosa a much less common species.…”
Section: Discussionsupporting
confidence: 89%
“…Each collected specimen was documented with an Olympus TG5 under water (when possible) and additionally in the laboratory, provided with a unique identifier (abbreviation of name, year, location, and number of specimen), and preliminarily identified with the help of available literature (e.g., [3][4][5]11,15,16,[20][21][22][23][24][25][26][27]). Gosliner et al [24] depict many undescribed species.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, there are currently eight synonyms for this species (Rosenberg & Bouchet 2012). However, recent molecular studies showed that P. pustulosa is likely to be a species complex with up to four molecular operational taxonomic units (Stoffels et al 2016). Therefore, this putative species complex and its geographic distribution needs further investigation.…”
Section: Phyllidia Coelestismentioning
confidence: 99%
“…The main distinction is associated with the outer longitudinal black bands: in the collected specimen, these bands are shorter and connect with the radial lines to create an inverted "V". As Phyllidia can be highly variable (Stoffels et al 2016), it is not possible to confirm the taxonomic status without further molecular or anatomical review.…”
Section: Phyllidia Coelestismentioning
confidence: 99%